2002
DOI: 10.1046/j.1365-2958.2002.03105.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐stranded RNA‐mediated gene silencing of cysteine proteases (falcipain‐1 and ‐2) of Plasmodium falciparum

Abstract: SummaryMalaria remains a public health problem of enormous magnitude, affecting over 500 million people every year. Lack of success in the past in the development of new drug/vaccines has mainly been attributed to poor understanding of the functions of different parasite proteins. Recently, RNA interference (RNAi) has emerged as a simple and incisive technique to study gene functions in a variety of organisms. In this study, we report the results of RNAi by double-stranded RNA of cysteine protease genes ( falc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 37 publications
1
64
0
1
Order By: Relevance
“…The truncated fragment of H. armigera haapn1 was subcloned in pGEM-Te and used for the preparation of dsRNA. As a control, the gene for falcipain of P. falciparum cloned in pGEM-T was used as described earlier (18). The pGEM-Te-cloned fragments were amplified by PCR using vector-specific universal and reverse primers (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The truncated fragment of H. armigera haapn1 was subcloned in pGEM-Te and used for the preparation of dsRNA. As a control, the gene for falcipain of P. falciparum cloned in pGEM-T was used as described earlier (18). The pGEM-Te-cloned fragments were amplified by PCR using vector-specific universal and reverse primers (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…The pGEM-Te-cloned fragments were amplified by PCR using vector-specific universal and reverse primers (Promega). The PCR product was purified (Qiagen GmbH) and used as DNA template for dsRNA preparation after the in vitro transcription procedure described by us (18). The T7 and SP6 RNA polymerases (MBI Fermentas) were used to generate single strand sense RNA and antisense RNA, respectively, from the DNA.…”
Section: Methodsmentioning
confidence: 99%
“…To date, RNAi related events have been recognised in almost all eukaryotic animals including algae [202], yeast [151], protozoans [11,27,94,118], plants [43,196], insects [2,17,26,77,100], fish [29,131] and in mammals [38,48,121,198].…”
Section: Discovery and Current Understandings Of Rnaimentioning
confidence: 99%
“…In T. brucei, a combination of efficient RNAi and a tight tet-regulated transcription is routinely applied for large scale analysis of genome function. In contrast, the efficiency of RNAi in apicomplexans is still a matter of debate [85,86], even if previous and more recent studies have reported the successful use of antisense/ribozyme in T. gondii [87][88][89] and some studies have suggested that the mechanism of RNAi can operate in the malaria parasites [90][91][92].…”
Section: Experimental Approaches and Tools Developed To Regulate Genementioning
confidence: 99%